2021
DOI: 10.1002/app.52086
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of sodium alginate/bifidobacterium probiotic biohybrid material used in tissue engineering

Abstract: Mechanical properties" are crucial for biodegradable and/or nonbiodegradable materials used in tissue engineering applications. In this study, bio-hybrid films were produced by using both Bifidobacterium animalis subsp. lactis BB-12 probiotic strain and Bifidobacterium infantis in combination with sodium alginate (SA), which demonstrates biocompatibility and facilitated gelation properties. Bio-hybrid films were characterized by using different methods. Based on the spectroscopic and mechanical analysis, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Recent research has revealed that the pairing of Ecm-Alginate and Bifidobacterium BB-12 and Bifidobacterium Infantis strains can enhance the antibacterial and anti-inflammatory properties of the Bifidobacterium BB-12 and Bifidobacterium Infantis strains , thereby exhibiting some degree of anti-cancer activity. This phenomenon can be attributed to the interaction between the peptidoglycan on the extracellular polysaccharide cell membrane of the Bifidobacterium BB-12 and Bifidobacterium Infantis strains and Ecm-Alginate [ 130 ]. Zheng et al observed that colonization of the TME by engineered Salmonella induced the infiltration of rich immune cells (such as monocytes/macrophages and neutrophils) through TLR4 signal transduction, and Salmonella colonized in the tumor caused the functional activation of tumor macrophages with the M1 phenotype through the secretion of Vibrio vulnificus flagellin B (FlaB) and mutual reduction in the inhibitory activity of M2-like macrophages, thereby strengthening the effect of immunotherapy [ 131 ].…”
Section: The Potential Clinical Value Of Targeting Intratumoural Micr...mentioning
confidence: 99%
“…Recent research has revealed that the pairing of Ecm-Alginate and Bifidobacterium BB-12 and Bifidobacterium Infantis strains can enhance the antibacterial and anti-inflammatory properties of the Bifidobacterium BB-12 and Bifidobacterium Infantis strains , thereby exhibiting some degree of anti-cancer activity. This phenomenon can be attributed to the interaction between the peptidoglycan on the extracellular polysaccharide cell membrane of the Bifidobacterium BB-12 and Bifidobacterium Infantis strains and Ecm-Alginate [ 130 ]. Zheng et al observed that colonization of the TME by engineered Salmonella induced the infiltration of rich immune cells (such as monocytes/macrophages and neutrophils) through TLR4 signal transduction, and Salmonella colonized in the tumor caused the functional activation of tumor macrophages with the M1 phenotype through the secretion of Vibrio vulnificus flagellin B (FlaB) and mutual reduction in the inhibitory activity of M2-like macrophages, thereby strengthening the effect of immunotherapy [ 131 ].…”
Section: The Potential Clinical Value Of Targeting Intratumoural Micr...mentioning
confidence: 99%
“…However, it is crucial for biodegradable materials to possess good mechanical properties for applications in specialty fields, such as tissue engineering. 17 …”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial for biodegradable materials to possess good mechanical properties for applications in specialty elds, such as tissue engineering. 17 Synthetic polymers can be easily tailored, designed and chemically modied, as compared to natural polymers. In view of this, the synthesis, characterization, commercialization, and application of biodegradable synthetic polymers have received extensive attention.…”
Section: Introductionmentioning
confidence: 99%